FAKTOR-FAKTOR YANG MENENTUKAN NIAT KONSUMEN UNTUK MELAKUKAN PEMBELIAN KEMBALI PRODUK DAN JASA - I Gusti Agung Ketut Sri Ardani (Forum Manajemen, 2017)
The main key to winning the competition is understand and satisfy the needs and desires of consumers through the delivery of products or services quality and competitive prices, It is aimed so that consumers do not switch to other companies that will create consumer loyalty. Customer decisions to make repurchases are complex and involve cost performance and co-positive considerations. Producer are interested to know how buyers / consumers make a purchase and purchase decision as well as the factors that determine repurchase. Many factors that determine consumer intention to repurchase products and services, in this presentation only discussed five factors that include: 1) Physical Environment, 2) Social Environment, 3) Time Perspective, 4) Purchasing Objectives, 5) Mood.